PRODUCTION AND OPTIMIZATION OF SIDEROPHORE PRODUCING PSEUDOMONAS SPECIES ISOLATED FROM TARAI REGION OF UTTARAKHAND - TARUN SHARMA; NAVIN KUMAR; NISHANT RAI (International Journal of Pharma and Bio Sciences, 2016)
A total thirty five rhizospheric bacteria were isolated from Tarai region of Uttarakhand, India. Among isolated strains, eight isolates shown siderophore production on succinic acid medium and chromo azural S agar medium plate. Three isolates were found to produce more than 60% siderophore units (SU). Amongst them PB19 was found to be the most efficient siderophore producer (78% SU) was identified as Pseudomonas spp. Maximum siderophore production was observed at pH 7 and temperature 29ËšC. Glucose as carbon source was found to stimulate bacterial growth as well as siderophore production. Lysine was found to be optimum for siderophore production. Maximum siderophore yield was obtained with urea at 0.6gL-1 as independent nitrogen source. Iron concentration up to 20 µM was found to be optimum for siderophore production. Shake flask studies revealed that the siderophore production starts after 6 h of growth and reached to maximum productivity of 70.43% SU after 30 hrs. Both types of siderophore produced by selected isolates i.e. wine red color and yellow color formation in supernatant indicated production of hydroxamate type (pyoverdine) and presence of catecholate or phenolate type (pyochelin) siderophore respectively. The present study reveals Pseudomonas strain as a promising candidate for crop improvement and protection due to its PGPR activities.